Civic Disposition Based on Ecological Citizenship: A Case Study at SMP Negeri 1 Wirosari - Marisa Zakiyya Amini; Wibowo Heru Prasetiyo; Sri Gunarsi (JED (Jurnal Etika Demokrasi), 2022)
Developing values and morals based on ecological issues provides opportunities for character development models in the educational environment. This study explores the character values of ecological citizenship generated in the Adiwiyata program at SMP Negeri 1 Wirosari. Program Adiwiyata or the green school program can be considered to formalise environmental care values. The research method employed a qualitative approach with a case study research design. Research informants were selected by purposive sampling involving the principal, the head of Adiwiyata, teachers, and students. Data were collected through observation, interviews, and documentation. Interactive data analysis techniques and data validity triangulation used Nvivo 12 plus software. The results show that the Adiwiyata program forms the character of ecological citizenship, including environmental concern, responsibility, mutual cooperation, discipline, and religion. The findings emphasize the potential for increasing ecological citizenship by providing environmental education materials, extracurricular activities, teacher role models, rewards, punishments, and collaboration with various parties. School principals should assess the adiwiyata program regularly so that it will be even better in the future and for teachers to increase motivation in fostering students to develop civic disposition values through adiwiyata activities.